EE-MAC: An Energy-Efficient MAC Scheme for Mobile Ad Hoc Networks - Sivanesan, P.; Thangavel, S.; J. Suresh (Asian Journal of Electrical Sciences, 2012)
A mobile ad hoc network (MANET) is a network where mobile nodes communicate with each other via wireless medium directly or indirectly with the help of other nodes control. Nodes in a MANET are free to move and organize themselves in an arbitrary fashion. Energy-efficient design in MANETs is a significant challenge due to its characteristics such as distributed control, constantly changing network topology, and mobility with limited power supply. The IEEE 802.11 MAC protocol includes a power saving mechanism, but it has many limitations. A new energy-efficient MAC protocol (EE-MAC) is proposed in this paper. It is shown that EE-MAC performs better than IEEE 802.11 power saving mode and exceeds IEEE 802.11 with respect to balancing network throughput and energy savings.